Globalization and the Singapore curriculum : from policy to classroom - Gopinathan, S.; Lee, Christine Kim-Eng; Deng, Zongyi (Education Innovation Series, 2013)
This volume provides a multi-faceted and critical analysis of the Singapore curriculum in relation to globalization. First, it details reform initiatives established by the Singapore government to meet the challenges posed by globalization. Next, Globalization and the Singapore Curriculum presents how these reforms have been translated into programs, school subjects and operational frameworks and then examines, in turn, how well these have been implemented in schools and classrooms across the country. Through this examination, the book reveals how the initiatives, together with their curricular translation and classroom enactment, reflect on the one hand global features and tendencies and, on the other, distinct national traditions, concerns and practices. It brings to light a set of issues, problems and challenges that not only concern policymakers, educators and reformers in Singapore but also those in other countries as well. Written by curriculum scholars, policy analysts, researchers and teacher educators, Globalization and the Singapore Curriculum offers an up-to-date reference for postgraduate students, scholars and researchers in the areas of curriculum and instruction, comparative education, educational sociology, educational policy and leadership in Singapore, the Asia Pacific region and beyond. It also offers a vital contribution to the story of modern education around the globe: providing international students, scholars and researchers valuable insights into curriculum and curriculum reform for the 21st century.